Pengembangan Fasilitas Bimbingan Akademik Online pada Portal Akademik Universitas Andalas - Husnil Kamil; Iqbal Nawa Zaki (Ikatan Ahli Informatika Indonesia, 2020)
Academic portal of Universitas Andalas is an information system that act as an academic information integrator as well as a means of communication between the campus academic community. Based on preliminary analysis that has been done, the Academic portal of Universitas Andalas functional is still not optimal, especially in terms of academic guidance facilities. The online academic guidance at Universitas Andalas so far still relied on social media applications which are generally in the form of chat applications. Social media usage as a communication facility for online academic guidance is not documented well. Meanwhile, academic guidance documentation is needed due to one of the accreditation assessments components by the National Higher Education Accreditation Board. Besides academic guidance is also a requirement for getting exam card for students. Academic guidance which done face to face, requires students to meet with the supervisor to get signature on the test card. There are several cases where students have not been able to meet face-to-face with a supervisor which resulted in being unable to take the exam. The solution to the problem above is to develop an online academic guidance facility in academic portal of Universitas Andalas. This facility is fulfilled by creating chatting facilities as social media or chatting applications that are often used. For this reason, research is needed to develop online academic guidance facilities. This research aims to develop an online academic guidance facility in academic portal of Universitas Andalas so that academic guidance can be run optimally and are documented. The research method used is a preliminary study to obtain accurate information and data needed, literature study, analysis and system design, implementation, and testing. The testing method used in this study uses black box testing. There are 18 functional requirements obtained based on the analysis. This research has created a portal that has an online academic guidance facility in academic portal of Universitas Andalas. The test results of the system show that the functional system is in accordance with the functional requirement.